Encephalization and Division of Labor by early humans - John Hartwick (Queen's University, Department of Economics, 2007)
We draw on Ricardian comparative advantage between distinct persons to map out the division of labor among proto-humans in a village some 1.7 million years ago. A person specialized in maintaining a cooking fire in the village is of particular interest (Ofek [2001]). We are also interested in modelling hunting by village males in teams. The large issue is whether and how specialization (division of labor) and interpersonal trade might have driven brain-expansion in early humans.
Keywords: A14; D51; J22; 330; early humans; division of labor; brain expansion; Arbeitsteilung; Anthropologie; Vorgeschichte